Selected decisions and selected documents of the International Monetary Fund: thirteenth issue, April 30, 1987 - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1987)
The book contains the decisions, interpretations, and resolutions of the Executive Board of Governors of the International Monetary Fund, and related documents, to frequent reference are made in the current activities of the Fund.
Some issues have accompanying annex volumes.
usc 02/09/2021
Ref.
Keywords: International finance; IMF; Internationale financiën.; International finance; FUNDS; RESOLUTIONS AND DECISIONS; DOCUMENTS